1960
DOI: 10.1111/j.1476-5381.1960.tb01203.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substance P on the Superior Cervical Ganglion of the Cat

Abstract: Intra-arterial injections of substance P in doses from 10 to 30 units potentiated the response of the nictitating membrane to submaximal stimulation of the preganglionic sympathetic nerve, while higher doses (30 to 100 units) usually depressed the response. The stimulating action of acetylcholine on the superior cervical ganglion (as judged by the response of the nictitating membrane) was also potentiated by substance P. The responses of the nictitating membrane to adrenaline, noradrenaline and tyramine were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Larger amounts of Substance P depress ganglionic transmission (14). No stimulation of the quiescent ganglion is observed.…”
Section: Ganglion-stimulating Substancesmentioning
confidence: 96%
“…Larger amounts of Substance P depress ganglionic transmission (14). No stimulation of the quiescent ganglion is observed.…”
Section: Ganglion-stimulating Substancesmentioning
confidence: 96%
“…With 5000 units, spontaneous, but not induced, activity was reduced (28). Ganglionic transmission in the superior cervical ganglion of the cat was not affected by high doses of the purified SP (19), although a dual 753 reported using impure extracts (140,166,167). Caspers (10,168,169) correlated behavioral with bioelectrical changes in the unanesthetized rat after administration of an impure SP extract.…”
Section: Journal Of Pharmaceutical Sciencesmentioning
confidence: 69%
“…(a) Action of substance P on peripheral nervous structures : Beleslin and co-workers (14) found that intraarterial inj ections of substance P in doses from 10 to 30 units potentiated the response of the nictitating mem brane to submaximal stimulation of the sympathetic preganglionic nerve, whereas higher doses usually depressed the response. The stimulatory actions of acetylcholine on the superior cervical ganglion and of epineph rine, norepinephrine, and tyramine on the nictitating membrane were also potentiated by the polypeptide.…”
Section: Bradykinin -Like Popypeptidesmentioning
confidence: 99%